Enrollment and completion rates of a nationwide guided digital parenting program for children with disruptive behavior before and during COVID-19 - Lintula, Sakari; Sourander, Andre; Hinkka-Yli-Salomaki, Susanna; Ristkari, Terja; Kinnunen, Malin; Kurki, Marjo; Marjamaki, Altti; Gyllenberg, David; Kim, Hyoun; Baumel, Amit (SPRINGER, 2025)
Our aim was to study enrollment and completion levels for the internet-based and telephone-assisted Finnish Strongest Families Smart Website (SFSW) parent training intervention, for parents of young children with disruptive behavior before and after the COVID-19 lockdown period. Population-based screening was carried out on 39,251 children during routine check- ups at 4 years of age. The parents of children scoring at least 5 on the Strengths and Difficulties Questionnaire were assessed against inclusion and exclusion criteria. Associations with enrollment or completion were analyzed using logistic regression models. The effects of COVID-19 restrictions on these were estimated using interrupted timeseries analysis. Of 39,251 families, 4894 screened positive and met the eligibility criteria. Of those, 3068 (62.6%) decided to enroll in the SFSW program and 2672 (87.1%) of those families completed it. The highest level of disruptive behavior (OR 1.33, 95% CI 1.12-1.57, p < 0.001) and overall severity of difficulties (OR 2.22, 95% CI 1.91-2.57, p < 0.001) were independently associated with enrollment. Higher parental education was associated with enrollment and completion. Higher paternal age was associated with enrollment, and parent depressive symptoms with non-completion. The SFSW enrollment did not significantly change following the COVID-19 restrictions, while the completion rate increased (COVID-19 completion OR 1.75, 95% CI 1.22-2.50, p = 0.002). Guided digital parenting interventions increase the sustainability of services, by addressing the child mental health treatment gap and ensuring service consistency during crisis situations.